Diskursus Hukum Islam dalam Konteks Keindonesiaan: Memahami Kembali Nilai-Nilai Substantif Agama - M. Ikhwan; Anton Jamal (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2021)
This paper explain the discourse of Islamic law in the Indonesian context in order to understand the substantive values of religion in national life. The development of the times raises the complexity of problems in life, including the presence of Islamic law in the nation-state, this of course requires a comprehensive discourse in order to answer each of these problems. This paper uses a qualitative research method with a narrative approach by referring to secondary sources so that it can be concluded. First, the formulation of Islamic law in Indonesia needs to be considered in terms of prioritizing the application of the noble values of religion itself (substantive). Second, the role of religion is very large in public life, hence the exclusion of religion from the private sphere or vice versa (placing religious law into the public sphere) needs to be viewed from various aspects. Third, the formalization of Islamic law in several perspectives of the Indonesian legal system is relatively difficult to materialize because of historical, ideological, sociological, political, juridical, religious and cultural considerations, both at the national and international levels.